Methodology of development of didactic education with the use of multimedia technologies - Jumabaevna, Xamidova Nilufar; Tursunbaevna, Rasulkulova Kamola; Shuxratovna, Rizaeva Kamola (International Journal of Psychosocial Rehabilitation, 2020)
Today, progress can not be imagined without information and communication technologies. Great attention is paid to the issues of informatization of education in Uzbekistan. In particular, in order to improve the quality of general secondary education through the development, improvement and introduction of e-learning resources on the basis of information and communication technologies in our country, the Center for the development of multimedia secondary education programs was established under the Ministry of public education of the Republic of Uzbekistan.Today's pedagogy requires further colorization and enrichment of methods of cultivation in the field of education, proper and productive use of pedagogical technologies. In particular, the use of multimedia in teaching foreign language subjects plays an important role in achieving the intended goal.